Custodia compartida en la terminación del vínculo matrimonial voluntario respecto a los menores, eximiendo el derecho a proponer acciones judiciales por juicio de alimentos - Apolo Maldonado, Valeria Salomé (2024)
The research work focuses on shared custody in the termination of the voluntary marital relationship with respect to minors, with the particularity of exempting the right to propose legal actions for alimony. Shared custody is a parenting modality that seeks to guarantee the equality and active participation of both parents after a separation or divorce. It seeks that the children maintain a close and meaningful relationship with both parents to promote their emotional stability and well-being. In a shared custody agreement, children spend regular time with each parent, ensuring a constant and relevant presence in their growth. It is based on the premise that both parents are equally important in the children's lives, and their collaboration is crucial for their proper development. The implementation of shared custody may vary according to the circumstances and preferences of each family, with some opting for an equal distribution of time, while others prefer a more flexible schedule. The benefits associated with shared custody include greater emotional stability for the children, belonging and security by maintaining a close relationship with both parents, as well as improved communication and cooperation between parents, decreasing conflict in the family environment. It also encourages shared parental responsibility in making important decisions about the education and welfare of the children. The exemption from the right to propose legal actions for alimony implies that, in a shared custody agreement or termination of the marital relationship, neither parent can file lawsuits to modify alimony in the future. This clause seeks to bring stability and predictability to the lives of the children, avoiding legal disputes over child support and promoting cooperation between the parents. It is essential to have legal advice to fully understand the implications of this exemption and to ensure that the agreement is fair and equitable to both parties, ensuring the welfare of the children. In some countries, this clause may not be allowed or require the approval of a judge to be valid, so it is necessary to comply with the corresponding legal requirements according to the applicable jurisdiction.